Differential degradation of BDE-3 and BDE-209 by the Shewanella oneidensis MR-1-mediated Fenton reaction. (March 2021) - Shi, Meimei; Xia, Kemin; Peng, Zhaofeng; Jiang, Yongguang; Dong, Yiran; Shi, Liang
Abstract: Shewanella oneidensis MR-1 is a bacterium that reduces ferric iron [Fe(III)] for respiration. The degradations of the persistent organic pollutants BDE-3 and BDE-209 by the S. oneidensis MR-1-mediated Fenton reaction with three Fe(III) sources were systematically compared in this investigation. Under the condition tested, neither BDE-3 nor BDE-209 negatively impacted the bacterial growth or the bacterial ability to produce the Fenton reactants Fe(II) and H2 O2 . However, more BDE-3 was degraded than BDE-209 by the reaction under the same condition. This observed differential degradation was most likely attributed to the different hydrophobic properties between BDE-3 and BDE-209. Compared to BDE-3, BDE-209 was more hydrophobic and more resistant to the degradation. Moreover, degradations of both BDE-3 and BDE-209 were inhibited by addition of HO ● scavengers as well as substitution of ferrihydrite with nitrate or omission of ferrihydrite in the reactions. Finally, monobromophenol and hydroxylated BDE-3 were identified as the products from BDE-3 degradation and hydroxylated BDE-47 and dibromophenol were identified as the products from BDE-209 degradation, which showed that both BDE-3 and BDE-209 were mainly degraded by HO ● via OH-addition. Taken together, this is the first report that the S. oneidensis MR-1-mediated Fenton reaction differentially degrades BDE-3 and BDE-209. Highlights: BDE-3 and BDE-209 do not impact bacterial growth or production of Fenton reagents. Bacterium-mediated Fenton reaction differentially degrades BDE-3 and BDE-209. Differential degradation is most likely attributed to the hydrophobicity of BDEs. The more hydrophobic, the more resistant to degradation. OH-addition is a main mechanism for degrading both BDE-3 and BDE-209.